Evidence-Based Education in Discourse around the Concept of Bildung - Topolovčan, Tomislav; Dubovicki, Snježana (Revija za elementarno izobraževanje, 2024)
The aim of this study lies in the use of theoretically comparative and historically methodological approaches to elaborate, compare, and recapitulate the features, history and the relationship of evidence-based education and the concept of Bildung. The relationship of the continental European didactic and Anglo-American curricular tradition, as well as to the meaning of teacher autonomy and (inter)national external evaluations of student achievements will be given special attention. Evidence-based education degrades teacher autonomy. Constituting the synergy of these two concepts can be considered the contemporary Holy Grail of education, which will probably not be found in the theoretical-methodological differences.